Effects of wettability on explosive boiling of nanoscale liquid films: Whether the classical nucleation theory fails or not?. (April 2019) - Wang, Yan-Hong; Wang, Shao-Yu; Lu, Gui; Wang, Xiao-Dong
Highlights: Phase change behaviors of nanoscale liquid films are studied via MD simulations. A critical thickness is proposed to distinguish the macro-micro boiling transition. The critical thickness is found to be 10.34 nm for water. Abstract: Two main reasons including practical and scientific significance continuously motivate the studies of explosive boiling of nanoscale liquid films. Whether the nanoscale explosive boiling agrees with classical nucleation theory is still an open issue. In this work, we study the effects of surface wettability on the explosive boiling of nanoscale liquid films using molecular dynamics simulations. A critical film thickness is proposed to address the debate of whether the classical nucleation theory fails in nanoscale boiling. The explosive boiling modes and dynamics are summarized with the phase diagram based on various simulation cases, considering the effects of surface wettability, film thickness, and surface superheat. When the films thickness exceeds the critical thickness, hydrophobic surfaces are more favorable for explosive boiling, which still agrees with the classical nucleation theory. However, a much higher superheat is required to trigger the explosive boiling of a thin liquid film when its thickness is less than the critical thickness on hydrophobic surfaces, which consists with previous molecular dynamics simulations. Furthermore, we also find that the explosive boiling is trigged faster for films on hydrophilic surfaces than those on hydrophobic surfaces with the same superheat owing to the lower Kapitza thermal resistance. With such heat transfer superiority, hydrophilic surfaces can heat liquid films faster to explosion. The deliveries of this work and the concept of the critical thickness might help to understand the still fledgling field of nanoscale boiling phase change and its relevant mechanisms.